Nitrogen‐Rich Carbonaceous Materials for Advanced Oxygen Electrocatalysis: Synthesis, Characterization, and Activity of Nitrogen Sites. (31st May 2022) - Wu, Bin; Meng, Haibing; Morales, Dulce M.; Zeng, Feng; Zhu, Junjiang; Wang, Bao; Risch, Marcel; Xu, Zhichuan J.; Petit, Tristan
Abstract: Nitrogen‐doped carbons are among the fastest‐growing class of materials used for oxygen electrocatalysis, namely, the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER), thanks to their low cost, environmental friendliness, excellent electrical conductivity, and scalable synthesis. The perspective of replacing precious metal‐based electrocatalysts with nitrogen‐doped carbon is highly desirable for reducing costs in energy conversion and storage systems. In this review, the role of nitrogen and N‐induced structural defects on the enhanced performance of N‐doped carbon electrocatalysts toward the OER and the ORR as well as their applications for energy conversion and storage technologies is summarized. The synthesis of N‐doped carbon electrocatalysts and the characterization of their nitrogen functional groups and active sites for the conversion of oxygen are also reviewed. The electrocatalytic performance of the main types of N‐doped carbon materials for OER/ORR electrocatalysis are then discussed. Finally, major challenges and future opportunities of N‐doped carbons as advanced oxygen electrocatalysts are highlighted. Abstract : Nitrogen‐doped carbon electrocatalysts have shown rapid progress for the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER), accelerating their applications for energy conversion and storage technologies. This review summarizes the role of nitrogen sites in OER/ORR and provides a comprehensive overview of their synthesis and characterization. The most recent N‐doped carbon materials for advanced oxygen electrocatalysis are particularly emphasized.